Pathways and Strategies for Integrating Labor Education into Nautical English Curriculum in Higher Vocational Colleges - Jing, Zhou (Journal of Research in Vocational Education, 2025)
With the global shipping industry transitioning towards intelligent and green development, and the continuous increase in demands for the comprehensive quality of seafarers, the drawbacks of the traditional Nautical English teaching in higher vocational colleges, which “emphasizes language skills over professional attributes,” are becoming increasingly apparent. Based on the dual backgrounds of “Curriculum Ideology and Politics” and “Industry-Education Integration,” this paper deeply explores the necessity and feasibility of organically integrating the core connotations of labor education into Nautical English teaching. The research constructs a theoretical model of three-dimensional integration of “value shaping, knowledge imparting, and skill cultivation,” and systematically proposes specific implementation paths and strategies from four dimensions: curriculum objective reconstruction, teaching content reorganization, teaching model innovation, and evaluation system reform. Combining personal teaching practice, the author uses a typical teaching unit as an example to demonstrate how to infiltrate the labor spirit into the Nautical English classroom, aiming to provide a referential plan for cultivating new-era maritime talents with both proficient English communication skills and excellent labor literacy and firm professional faith.